Development of electronic trip unit for converter protection : modulation for cascaded H-bridge inverters under fault operations - Hla Hla Khaing (2016)
Marine electric propulsion systems in ships commonly use medium voltage (MV) converters to drive variable-speed electrical propulsion motors connected to propellers. In the recently year, different topologies of MV converter are developed and built by the marine industry including Rolls-Royce. Among these topologies, the cascaded H-bridge (CHB) inverter is one of the most popular and mature topologies in the industry. Its operation and control system are thoroughly analysed in Rolls-Royce@NTU Corporate Lab. Due to its multi-level output voltages, it has a low distortion and is very useful for high power drives in marine systems. Despite the advantages of CHB inverter, its large number of components required increases the fault probability. Among different types of fault, switch fault that strongly damages the health of converter is mainly focused on this project. Two fault tolerance pulse width modulation (PWM) methods (phase-shifted PWM (PS-PWM) and level-shifted PWM (LS-PWM)) are used to remain the balanced currents in the CHB inverter while operating it under the faulty condition without shutting down the system. Simulation and experimental results show the effectiveness of PS-PWM and LS-PWM methods, which significantly improves the reliability and health of the CHB inverter.